The Role of Family Da'wah in Children's Islamic Moral and Personal Education: Analysis of Al-Usrah Fiqh in the Era of Digital Globalization - Rabi’atul Adawiah Azman (STIT Attaqwa, 2026)
Digital globalization has brought major changes to the lifestyle of Islamic families, especially in the formation of children's Islamic morals and personality. Continuous exposure to digital media and global content without value filters has given rise to various moral and behavioral challenges, as well as weakening the role of the family as a medium of tarbiah and da'wah. In this context, fiqh al-usrah provides an important framework in understanding parents' responsibilities for children's moral education. This study aims to analyze the role of family da'wah in children's Islamic moral and personal education based on the perspective of fiqh al-usrah in the era of digital globalization. Specifically, this study examines the challenges of forming children's morals in the digital environment and identifies effective family preaching approaches according to the principles of fiqh al-usrah. This study uses a qualitative approach through document analysis and study highlights of writings related to fiqh al-usrah, family da'wah, moral education and the influence of digital media. The results of the study found that strengthening the role of parents as preachers in the family, consistently practicing moral modeling and implementing a preaching approach based on wisdom and digital reality are the main elements in the formation of children's Islamic personalities. It is hoped that this study can contribute to the strengthening of the family da'wah framework based on fiqh al-usrah as a practical guide in facing children's moral challenges in the era of digital globalization.